2019
DOI: 10.11114/jets.v7i9.4294
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pilates Reformer Exercises to Tennis Skills on Tennis Players

Abstract: The aim of this study is to determine the effect of reformer pilates trainings on ITN tennis test regarding the elite women aged 16-18 years. The research is done for voluntary participation of 14 elite female tennis players, whose age of training is 10,25 ± 1,72 years and average age 17,35 ± 0,77 years, All athletes were tested on the first day, then they were randomly divided into control (n=7) and experimental (n=7) groups. 90 minutes of pilates training sessions were performed for 3 days/week during eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Gul's study evaluated tennis players' ability to reach the ball on time in parallel and cross strokes and faster recovery for the next shot. They found that these skills increased after eight weeks of Pilates practice (25). For cue athletes, it is important to keep the shoulders and torso stable in certain positions to ensure accurate cue alignment and movement (6).…”
Section: Effects Of Pilates On Players' Scoresmentioning
confidence: 99%
“…Gul's study evaluated tennis players' ability to reach the ball on time in parallel and cross strokes and faster recovery for the next shot. They found that these skills increased after eight weeks of Pilates practice (25). For cue athletes, it is important to keep the shoulders and torso stable in certain positions to ensure accurate cue alignment and movement (6).…”
Section: Effects Of Pilates On Players' Scoresmentioning
confidence: 99%